The study of the paranemic crossover (PX) motif in the context of self-assembly of DNA 2D crystals. Issue 30 (12th July 2016) - Shen, Weili; Liu, Qing; Ding, Baoquan; Shen, Zhiyong; Zhu, Changqing; Mao, Chengde
Abstract : The DNA paranemic crossover (PX) motif has been examined as building blocks for construction of DNA 2D arrays and the optimal design has been discovered. Abstract : This manuscript systematically studies the self-assembly behavior of the paranemic crossover (PX) motif in the context of DNA 2D crystallization. The PX structure is a class of DNA nanomotifs that has been suggested as a model for DNA homologous recognition in cells and, more importantly, used as a cohesion mechanism/building block (tile) for DNA nanoconstruction. However, there is no vigorous examination on the relationship between structural variation and assembly behavior. The lack of this essential information prevents us from applying the PX motif to complex nanoconstruction. In this study, we have devised a system that allows us to systematically examine this relationship and found the best PX motif that best suits the assembly of 2D crystals.